Challenging the Cultural Mosaic: Shani Mootoo’s "Out on Main Street" - Schneider, Sebastian (Current Objectives of Postgraduate American Studies, 2012)
The essay examines the short story “Out on Main Street“ (1993) by Caribbean-Canadian author Shani Mootoo as an example of fictional contestations of the official policy of multiculturalism in Canada, which has been a major discourse in the realm of cultural affairs in Canada since the Canadian Multiculturalism Act of 1988. Canadian multiculturalism is often critiqued as a token policy aiming at keeping non-‘white’ Canadians from the ‘white’ cultural center of Canadian society. The discourse of multiculturalism is often conceptualized by the spatial metaphor of the mosaic and thus implies rigid boundaries, in this case between ethno-cultural groups. Mootoo is read here as one among many contemporary non-‘white’ Canadian authors of fiction that draft alternative spatial orders to the cultural mosaic in their texts and thus offer ways of imagining Canadian society differently.